Case report: Altered pre-mRNA splicing caused by intronic variant c.1499 + 1G > A in the SLC4A4 gene - Liu, Yan; Sheng, Wenchao; Wu, Jinying; Zheng, Jie; Zhi, Xiufang; Zhang, Shuyue; Gu, Chunyu; Guo, Detong; Wang, Wenhong (Frontiers in Pediatrics, 2022)
Proximal renal tubular acidosis (pRTA) with ocular abnormalities is an autosomal recessive disease caused by variants in the Solute Carrier Family 4 Member 4 (SLC4A4) gene. Patients present with metabolic acidosis and low plasma bicarbonate concentration (3∼17 mmol/L). In addition, they are often accompanied by ocular abnormalities, intellectual disability, and growth retardation. The patient underwent whole exome sequencing (WES) and bioinformatics analysis of variant pathogenicity in this study. Then, a minigene assay was conducted to analyze the splicing site variant further. Compound heterozygous variants in the SLC4A4 gene (NM_003759.3), c.145C > T (p.Arg49*) and c.1499 + 1G > A, were detected by WES. The minigene assay showed an mRNA splicing aberration caused by the c.1499 + 1G > A variant. Compared with the wild type, the mutant type caused 4-base insertion between exons 10 and 11 of SLC4A4 after expression in HEK293 cells. In conclusion, the c.1499 + 1G > A variant in the SLC4A4 gene may be one of the genetic causes in the patient. Moreover, our study provides the foundation for future gene therapy of such pathogenic variants.